2018
DOI: 10.1029/2018ja025320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Variations of TEC at Disturbed and Quiet Time Using Nonlinear Dynamics Tools

Abstract: We analyze the underlying dynamics at three different latitudes of ionosphere through total electron content‐series for 4 months. The global dynamics reconstructed from the data is shown to be deterministic with low dimensional chaotic attractors at all the locations, and the dynamics is seen to be less complex at the midlatitude station with smaller dimension of correlation (CD) and maximum Lyapunov exponent (MLE). The influence of geomagnetic storms on the ionospheric dynamics is studied, by analyzing the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Eapen et al (2018) [39] reported their results on the search for TEC time series chaoticity using data from the MIT Madrigal database. They selected one location each from the low latitude, (28 • N and 82 • W), midlatitude, (40 • N and 119 • W), and high latitude (60 • N and 150 • W) for the period from 1 January to 30 April of the solar minimum year 2008.…”
Section: Chaos Theory and The Ionospherementioning
confidence: 99%
See 1 more Smart Citation
“…Eapen et al (2018) [39] reported their results on the search for TEC time series chaoticity using data from the MIT Madrigal database. They selected one location each from the low latitude, (28 • N and 82 • W), midlatitude, (40 • N and 119 • W), and high latitude (60 • N and 150 • W) for the period from 1 January to 30 April of the solar minimum year 2008.…”
Section: Chaos Theory and The Ionospherementioning
confidence: 99%
“…Correlation dimension of the deterministic chaos found in TEC time series by different authors under different conditions. The asterisk means that the values are the averages of those shown in Tables1 and 2of the paper mentioned(Eapen et al, 2018). " ---" indicate that the geomagnetic activity is not specified.…”
mentioning
confidence: 99%
“…In the literature, there are also studies that use detrended time series of TEC for a single station by using a broad spectrum of analysis tools, such as correlation dimension, Lyapunov exponent, and multifractals for the investigation of nonlinear or chaotic behavior of TEC (Chandrasekhar et al, 2016;Eapen et al, 2018;Kumar & Eapen, 2013). In Unnikrishnan et al (2006aUnnikrishnan et al ( , 2006b, surrogate data testing is applied to midlatitude TEC for disturbed and quiet ionosphere during daytime and nighttime.…”
Section: Introductionmentioning
confidence: 99%